Development of a Storytelling Stage Model Assisted by Role Mask Media to Strengthen the Self-Confidence of Fourth Grade Elementary School Students - Tangguh Veliana Puspitasari; Kuntoro; Ana Andriyani; Ine Kusuma Aryani (Elementary Teacher Education Program, Majalengka University, 2026)
The low level of self-confidence among elementary school students has become a significant issue affecting their participation and courage in the learning process. This study aims to develop a storytelling stage model assisted by role mask media that is valid, practical, and effective in strengthening the self-confidence of fourth-grade elementary school students. The research employed a Research and Development (R&D) method using the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 39 fourth-grade students at SD Negeri 1 Bantarwuni. Data were collected through questionnaires, interviews, and documentation, while data analysis used both quantitative and qualitative approaches. The results showed that the developed model achieved a validity score with an average of 3.41, categorized as valid. User responses were in the very good category, with an average score of 3.50 from teachers and 3.42 from students. The implementation of the model was also proven effective in improving students’ self-confidence, indicated by an increase in scores from 2.45 to 3.40 and the result of the paired sample t-test with a significance value of 0.000. The N-Gain Score of 0.65 indicates a moderate level of improvement. These findings suggest that the storytelling stage model assisted by role mask media can create an interactive and enjoyable learning environment and contribute to strengthening students' self-confidence in elementary schools.